Evolution of genomic structural variation and genomic architecture in the adaptive radiations of African cichlid fishes - Fan, Shaohua; Meyer, Axel (Frontiers in Genetics, 2014)
African cichlid fishes are an ideal system for studying explosive rates of speciation and the origin of diversity in adaptive radiation. Within the last few million years, more than 2000 species have evolved in the Great Lakes of East Africa, the largest adaptive radiation in vertebrates. These young species show spectacular diversity in their coloration, morphology and behavior. However, little is known about the genomic basis of this astonishing diversity. Recently, five African cichlid genomes were sequenced, including that of the Nile tilapia (Oreochromis niloticus), a basal and only relatively moderately diversified lineage, and the genomes of four representative endemic species of the adaptive radiations, Neolamprologus brichardi, Astatotilapia burtoni, Metriaclima zebra, and Pundamila nyererei. Using the tilapia genome as the reference genome, we generated a high-resolution genomic variation map, consisting of single nucleotide polymorphisms (SNPs), short insertions and deletions (indels), inversions and deletions. In total, around 18.8, 17.7, 17.0 and 17.0 million SNPs, 2.3, 2.2, 1.4 and 1.9 million indels, 262, 306, 162, and 154 inversions, and 3509, 2705, 2710 and 2634 deletions were inferred to have evolved in the N. brichardi, A. burtoni, P. nyererei and M. zebra respectively. Many of these variations affected the annotated gene regions in the genome. Different patterns of genetic variation were detected during the adaptive radiation of African cichlid fishes. For SNPs, the highest rate of evolution was detected in the common ancestor of N. brichardi, A. burtoni, P. nyererei and M. zebra. However, for the evolution of inversions and deletions, we found that the rates at the terminal taxa are substantially higher than the rates at the ancestral lineages. The high-resolution map provides an ideal opportunity to understand the genomic bases of the adaptive radiation of African cichlid fishes.